Sistemática e conservação de Miconia seção Miconia DC. (Melastomataceae) no estado de Minas Gerais, Brasil - Rezende, Allisson Rodrigues de (2012)
Miconia Ruiz & Pav. is the largest genus in Melastomataceae with about 1000 species distributed through the neotropics. The genus is characterized mainly by present baccate fruits, terminal inflorescences and petals with the apex rounded or emarginated. Miconia is divided in 12 sections, and Miconia is the largest section. The section is characterized by short and linear anthers, apex slightly attenuated and connective with ventral appendages. The study was based on 2282 specimens deposited in 15 herbaria. The section Miconia DC. is represented in Minas Gerais by 26 species: M. affinis DC., M. albicans (Sw.) Triana, M. burchellii Triana, M. calvescens DC., M. caudigera DC., M. chamissois Naudin, M. cipoensis R.Goldenb., M. cuspidata Naudin, M. elegans Cogn., M. fallax DC., M. ferruginata DC., M. herpetica DC., M. ibaguensis (Bonpl.) Triana, M. irwinii Wurdack, M. lepidota DC., M. leucocarpa DC., M. macrothyrsa Benth., M. matthaei Naudin, M. mendoncae Cogn., M. organensis Gardner, M. pennipilis Cogn., M. polyandra Gardner, M. prasina (Sw.) DC., M. pseudonervosa Cogn., M. rubiginosa (Bonpl.) DC. and M. stenostachya DC. Miconia matthaei is a new occurrence for Minas Gerais. We present descriptions, illustrations, identification key, data on flowering and fruiting, maps with patterns of distribution, and conservation status for the species of Miconia section Miconia in Minas Gerais state.